PENGARUH TRANSAKSI NON TUNAI TERHADAP EFEKTIVITAS PENATAUSAHAAN KEUANGAN PADA BADAN PENGELOLA KEUANGAN, PENDAPATAN ASET DAERAH KABUPATEN TAPANULI SELATAN - Ade Maya Mei Shanty (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
This study aims to determine the effect of non-cash transactions on the effectiveness of administration in the financial management agency, regional asset income in South Tapanuli Regency. The magnitude of the system of the effect of non-cash transactions on the effectiveness of administration in the financial management agency, regional asset income in South Tapanuli Regency. The sample of this research is 49 employees who are involved in financial management at the Financial Management Agency, Regional Asset Income in South Tapanuli Regency. From the results of simple regression testing, it is found that the non-cash transaction regression coefficient (X) = 0.405, this value means that the non-cash transaction variable (X) tends to have a direct effect on the effectiveness of financial administration at the Financial Management Agency, Regional Asset Income in South Tapanuli Regency, with the understanding that if the non-cash transaction variable (X) is increased by 100%, the effectiveness of financial administration at the Financial Management Agency, Regional Asset Income in South Tapanuli Regency will increase by 40.5%. The coefficient of determination (R Square) is 0.178. So it can be concluded that from the results of this study it can be seen that non-cash transactions (X) have an effect of 17.8% on the effectiveness of financial administration at the Financial Management Agency, Regional Asset Income in South Tapanuli Regency. While the remaining 82.2% is the influence of other variables outside of research such as compensation, attendance, staffing systems, and others.